Aggregate worker reallocation and occupational mobility in the United States: 1971 - 2000 - Giuseppe Moscarini; Francis Vella (Institute for Fiscal Studies (IFS), 2002)
We investigate the evolution and the sources of aggregate employment reallocation in the United States in the 1971-2000 March files of the Current Population Survey. We focus on the annual flows of male workers across occupations at the Census 3-digit level, the finest disaggregation at which a moving worker changes career and relocates to an observationally different technology. We find that the total reallocation of employment across occupations has been strongly procyclical and sharply declining until the early 1990s, before remaining relatively constant in the last decade. To reveal the sources of these patterns, while correcting for possible worker selection into employment, we construct a synthetic panel based on birth cohorts, and estimate various models of worker occupational mobility. We obtain five main results. The cross-occupation dispersion in labor demand, as measured by an index of net employment reallocation, has a strong association with total worker mobility. The demographic composition of employment, more specifically the increasing average age and college attainment level, explains some of the vanishing size and procyclicality of worker flows. High unemployment weakens the effects of individual worker characteristics on their occupational mobility. Worker mobility has significant residual persistence over time, as predicted by job-matching theory. Finally, we detect important unobserved cohort-specific effects; in particular, later cohorts have increasingly low unexplained occupational mobility, which contributes considerably to the downward trend in total employment reallocation over the last three decades.
Keywords: 330; Arbeitsmobilität; USA